Food safety knowledge attitude and practices of oncology nurses, in Lebanese hospitals - Angy, Mallah (2023)
BackgroundCancer patients undergoing chemotherapy treatment, have a higher risk to foodborne infections as compared to other populations. Oncology nurses, having a direct significant contact with these patients, could be the first information source concerning food safety and play a pivotal role in reducing these risks. ObjectiveThis study aims to assess the level of knowledge regarding food safety among oncology nurses, as well as their attitudes and practices in private hospitals in Lebanon. MethodsA self-administered questionnaire was filled by Oncology nurses (n = 134) working in eighteen private hospitals in Lebanon located in Mount Lebanon (n = 11) and Beirut (n = 7). ResultsOverall, oncology nurses scored 76%, 95%, 86.9% and 83.4% on the knowledge, attitude, and practices questions, and overall composite knowledge, attitude, practices (KAP) score, respectively. Knowledge scores were higher among nurses holding a graduate degree (mean = 85; p < 0.05), and those who attended a training course (mean = 79; p < 0.05). Attitude scores of nurses who read brochures were higher (p < 0.001). Attending conferences on food safety showed statistically significant effect on better practice scores (p < 0.001). ConclusionAccordingly, the findings highlight the need to develop standardized food safety curriculum and training necessary to allow oncology nurses to contribute to the education of cancer patients and decrease their risk of foodborne infection.